Phenological variations of avocado cv. Hass and their relationship with thermal time under tropical conditions - Ramírez-Gil, Joaquín Guillermo; Henao-Rojas, Juan Camilo; Diaz-Diez, Cipriano Arturo; Peña-Quiñones, Andrés Javier; León, Nicolas; Parra-Coronado, Alfonso; Bernal-Estrada, Jorge Alonso (Heliyon, 2023)
In recent years, the avocado has been one of the most dynamic fruits in the world market. In particular, cv. Hass stands out due to its productivity, nutritional quality, and acceptance. Under tropical conditions, weather elements, especially air temperature, and precipitation, affect the productivity and quality of cv. Hass. However, in tropical environments, many relationships between weather and phenological aspects of this cultivar are still unknown. Given this situation, our aim was to identify the variation and degree of association between the phenology of avocado cv. Hass and thermal time (TT) under low-latitude conditions. Eight commercial fields planted with cv. Hass grafted onto Antillean genotypes, located in an altitudinal transect between 1,700 and 2,500 m, were evaluated. The evaluation was carried out for three years and was focused on determining the differences in avocado phenological patterns associated with different environmental variables monitored by weather stations at each location. Air temperature data were used to calculate the base temperature (BT) using different methods for all phenological stages. Later the TT was determined for each stage and all locations. The results show that the duration of each phenological stage varies as a function of elevation (air temperature) and that the phenological stages overlap at the regional, crop field, and plant levels at different periods of the year, generating a high phenological variability but with specific patterns associated with temperature and precipitation. The BT for each phenological stage varied between 0.3 and 7.5 °C, and TT was found to vary depending on the method of calculation. Our work suggests that the generalization of a BT of 10 °C is not applicable for avocado cv. Hass crops under tropical conditions, specifically in the case of Colombia. Detailed studies of phenological relationships with respect to climatic variables will allow a better approximation of the productive behavior of avocado cv. Hass. •Hass avocado is subject to high variation in phenological stages under tropical conditions.•We demonstrated that the generalization of a base temperature of 10 °C does not apply under tropical conditions, specifically in the case of Colombia.•The duration of each phenological stage varies as a function of elevation (air temperature) and precipitation under tropical conditions.•Phenological stages overlap at the regional, crop field, and plant levels, generating a high phenological variability.